Network of MicroRNAs Mediate Translational Repression of Bone Morphogenetic Protein Receptor‐2: Involvement in HIV‐Associated Pulmonary Vascular Remodeling. Issue 5 (25th February 2018) - Chinnappan, Mahendran; Mohan, Aradhana; Agarwal, Stuti; Dalvi, Pranjali; Dhillon, Navneet K.
Abstract : Background: Earlier, we reported that the simultaneous exposure of pulmonary arterial smooth muscle cells to HIV proteins and cocaine results in the attenuation of antiproliferative bone morphogenetic protein receptor‐2 (BMPR2) protein expression without any decrease in its mRNA levels. Therefore, in this study, we aimed to investigate the micro RNA‐mediated posttranscriptional regulation of BMPR2 expression. Methods and Results: We identified a network of BMPR2 targeting micro RNAs including miR‐216a to be upregulated in response to cocaine and Tat‐mediated augmentation of oxidative stress and transforming growth factor‐β signaling in human pulmonary arterial smooth muscle cells. By using a loss or gain of function studies, we observed that these upregulated micro RNAs are involved in the Tat‐ and cocaine‐mediated smooth muscle hyperplasia via regulation of BMPR2 protein expression. These in vitro findings were further corroborated using rat pulmonary arterial smooth muscle cells isolated from HIV transgenic rats exposed to cocaine. More importantly, luciferase reporter and in vitro translation assays demonstrated that direct binding of novel miR‐216a and miR‐301a to 3′UTR of BMPR2 results in the translational repression of BMPR2 without any degradation of its mRNA. Conclusions: We identified for the first time miR‐216a as a negative modulator of BMPR2 translation and observed it to be involved in HIV protein(s) and cocaine‐mediated enhanced proliferation of pulmonary smooth muscle cells.